Decoding the conformation‐linked functional properties of nucleic acids by the use of computational tools. (19th May 2015) - Iacovelli, Federico; Falconi, Mattia
<x xml:space="preserve">Abstract</x> DNA and RNA are large and flexible polymers selected by nature to transmit information. The most common DNA three‐dimensional structure is represented by the double helix, but this biopolymer is extremely flexible and polymorphic, and can easily change its conformation to adapt to different interactions and purposes. DNA can also adopt singular topologies, giving rise, for instance, to supercoils, formed because of the limited free rotation of the DNA domain flanking a replication or transcription complex. Our understanding of the importance of these unusual or transient structures is growing, as recent studies of DNA topology, supercoiling, knotting and linking have shown that the geometric changes can drive, or strongly influence, the interactions between protein and DNA, so altering its own metabolism. On the other hand, the unique self‐recognition properties of DNA, determined by the strict Watson–Crick rules of base pairing, make this material ideal for the creation of self‐assembling, predesigned nanostructures. The construction of such structures is one of the main focuses of the thriving area of DNA nanotechnology, where several assembly strategies have been employed to build increasingly complex DNA nanostructures. DNA nanodevices can have direct applications in biomedicine, but also in the materials science field, requiring the immersion of DNA in an environment far from the physiological one. Crucial help in the understanding and planning of natural and artificial nanostructures is given by modern computer simulation techniques, which are able to provide a reliable structural and dynamic description of nucleic acids.